Photoperiodic response and callus formation of the isogenic E-genes soybean lines - Васильченко, М. С.; Авксентьєва, О. О.; Жмурко, В. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The paper presents the investigation results of callus formation processes of the eight isogenic from E-genes soybean Glycine max (L.) Merr. lines with different photoperiodic response. It is shown that all the lines are successfully introduced to the in vitro culture, but differ on the rate of primary callus formation. The isolines with short-day reaction are characterized by a faster rate of primary callus formation and the highest values of growth index (GI) compared with photoperiodic neutral lines. The GI changes during subculturing correlate with indicators of calli wateriness. It is discussed the interrelation photoperiodic response of isolines in vivo that is determined by the genotype features of the callus growth response in vitro.